Hormone and neurotransmitter receptor studies in the rat during pregnancy and the postpartum period - Glaser, Jonathan (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Medicine)) -- University of Stellenbosch, 1991.